LANDASAN FILOSOFIS DALAM SISTEM PENDIDIKAN: KAJIAN ALIRAN FILSAFAT DAN PARADIGMA HUMANISTIK, KRITIS, DAN TRANSFORMATIF - Paradipa; Yudo Handoko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the philosophical foundations within the education system through an analysis of major philosophical schools and the paradigms of humanistic, critical, and transformative education. The problem addressed in this research lies in the lack of comprehensive understanding of how philosophical perspectives shape educational goals, processes, and outcomes in contemporary contexts. Therefore, this study aims to explore the role and relevance of various philosophical streams in constructing educational paradigms that are responsive to human development and social change. This research employs a qualitative approach using the library research method, where data are collected from books, academic journals, and relevant scholarly sources, then analyzed descriptively and interpretatively. The findings reveal that humanistic philosophy emphasizes the development of learners’ potential and individuality, critical philosophy encourages awareness of social inequalities and fosters critical thinking, while transformative philosophy promotes education as a tool for social change and empowerment. These paradigms collectively provide a comprehensive framework for developing an education system that is not only academically oriented but also socially and morally responsive. Thus, integrating these philosophical foundations is essential for creating a holistic and meaningful educational practice